Thinking ahead: the Naval War College influence on warship design - Neves, Nuno Correia (2017)
The aim of this article is to study whether the United States Navy original and innovative practice of using the Naval War College, its staff and students, as a “think tank” to assist the Navy General Board on setting the path for the development of future warships was a long term advantage and constitutes a possible reference model for the cooperation between military academic institutions and high level decision making staffs on the defense sector.